2011
DOI: 10.1002/ppul.21621
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Lung Disease Surrogates in Detecting Chest CT Abnormalities in Children With Cystic Fibrosis

Abstract: Rationale Chest CT scans detect structural abnormalities in children with cystic fibrosis (CF), even when pulmonary function tests (PFTs) are normal. The use of chest CT is limited in clinical practice, because of concerns over expense, increased resource utilization, and radiation exposure. Quantitative chest radiography scores are useful in detecting mild lung disease, but whether they are sensitive to the presence of CT scan abnormalities has not been evaluated. Objective To determine in a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In school age children and adolescents with CF, Sanders and colleagues recently showed that CXRs were important predictors of future lung dysfunction, performing as well as CT scans 25 , and that Wisconsin and Brasfield CXR scores had excellent sensitivity for detecting abnormal chest CTs 26 . The Wisconsin CF Radiograph Scoring System was specifically developed as an alternative to older scoring systems such as the Brasfield to be sensitive to mild CF lung disease 19 , though neither system was developed to detect the very mild abnormalities now generally seen in infants and toddlers such as those in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In school age children and adolescents with CF, Sanders and colleagues recently showed that CXRs were important predictors of future lung dysfunction, performing as well as CT scans 25 , and that Wisconsin and Brasfield CXR scores had excellent sensitivity for detecting abnormal chest CTs 26 . The Wisconsin CF Radiograph Scoring System was specifically developed as an alternative to older scoring systems such as the Brasfield to be sensitive to mild CF lung disease 19 , though neither system was developed to detect the very mild abnormalities now generally seen in infants and toddlers such as those in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] An essential component for the clinical management of patients with CF is the capability to longitudinally monitor the progression of lung disease and therapeutic efficacy. Unfortunately, current clinical assessments of CF lung disease are either invasive (bronchoalveolar lavage, BAL [3,4]), expose patients to significant repeated doses of ionizing radiation (X-ray and/or Computed Tomography (CT))[5–7], or offer limited sensitivity to detect early-stage, regional lung disease (spirometry). Therefore, the development of a sensitive, non-invasive, and radiation-free method for assessing CF lung disease is the essential next step towards improving health care for patients with CF.…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes detected by CT scans often precede functional changes in children with CF, [1][2][3][4][5] and CT scanning may be a more sensitive method than measurement of lung function for detecting disease progression. 6,7 Furthermore, CT scanning is a potential outcome measure for CF clinical trials. 8,9 To provide quantitative information, CT images must be converted into numeric data to allow statistical comparison between scans.…”
mentioning
confidence: 99%